Effects of Deregulation and Consolidation of the Broadcast Television Industry - Stahl, Jessica Calfee (American Economic Review, 2016)
This paper exploits deregulation in the 1990s to estimate viewership and revenue effects of consolidation in broadcast television, then finds cost effects that explain the ownership structure given viewership and revenue effects. Results suggest that consolidation greatly increased profitability in an industry with otherwise declining profitability. Groups with broader national coverage attract more advertising per station. Joint ownership of two stations within a market and network ownership both allow for significant cost savings. There is some evidence that within-market consolidation allows stations to achieve local market power. However, both within-market and across-market consolidation appear to have boosted viewership, on net. (JEL G32, L13, L25, L51, L82, L88)